Designing tangible interaction using short-range RFID - Nordby, Kjetil; Morrison, Andrew (FormAkademisk, 2010)
Short-range Radio Frequency IDentification (SR-RFID) technology embedded in mobile phones offers interaction design practitioners the potential to design new forms of mobile experiences. The article presents a design oriented research study that seeks to develop affordances specifically in support of such practice. To do so the authors draw on Activity Theory. They present three levels of SR-RFID related design affordances: need related design affordances, instrumental design affordances and operational design affordances. Included also is what they label ‘RFID based Tap and Hold’; a term used so as to frame tangible interaction on SR-RFID. A generative and descriptive model of Tap and Hold is proposed, as is a set of input techniques derived from the Tap and Hold model. Overall, the study suggests opening out from functional views of SR-RFID to ones that view it as a technology applicable for designers exploring potential new interactions. This is important since such work may be used to support the generation of new designs, an area often overlooked in research on RFID.